## Trending News

# Algebra Help with Functions?

This is jibberish to me, I don't get it at all.

Evaluate each function for the value specified.

f(x) = x^2-x-2; find (a)f(0),(b)f(-2),and (c)f(1)

### 8 Answers

- 1 decade agoFavorite Answer
okay this is how i did it...all it do is plug in those numbers for x and then solve...

ex: f(0) 0^2-0-2 which comes out to be -2

f(-2) -2^2--2-2 or -2^2+2-2 b/c the 2 negatives make that a plus...so it comes out to be -4

f(1) 1^2-1-2 which comes out to be -2

did that make any sense...lol kinda hard to explain on a computer! hope it helped

- Anonymous1 decade ago
X^2 means X*X (or X times X) so you plug in the value of x into the full equation:

f(0)=0*0-0-2=0 times 0 minus 0 minus 2=-2

f(-2)=-2*-2-(-2)-2=4-(-2)-2=4+2-2=4

f(1)=1*1-1-2=-2

- 1 decade ago
Just substitute for x the values 0, (-2) and 1 respectively

in the expression on the right hand side of the equation.

Now go ahead and work it yourself. Good luck.

- Anonymous1 decade ago
f(0) means replacing every "x" in the function with "0":

so, if f(x) = x^2 - x - 2

then, f(0) = (0)^2 - 0 - 2 (square 0)

= 0 - 0 - 2 (go left to right)

= 0 - 2

= -2

do the others the same way

- How do you think about the answers? You can sign in to vote the answer.
- 1 decade ago
I'm not even in high school, but I picked up functions somewhere.

a) -2

b) +4

c) -2

Just keep in mind that you should understand the process instead of just going online for every piece of math homework. All you do here is just plug in the possible values for "x" into the function and solve away.

- 1 decade ago
f(x) = x^2-x-2; find (a)f(0),(b)f(-2),and (c)f(1)

okay so basically f(x) = x^2-x-2 so then when you have f(0) then you just replace x with 0 so f(0) =(0)^2-(0)-2 and same with b) f(-2) = (-2)^2-(-2)-2 and you just take away the brackets and solve the equation

Source(s): I listened in maths class - Sir N. NetiLv 41 decade ago
a.)

f(0) = (0)^2 - (0) -2

f(0) = 0 - 0 - 2

f(0) = -2

b.)

f(-2) = (-2)^2 - (-2) -2

f(-2) = 4 + 2 - 2

f(-2) = 4

c.)

f(1) = (1)^2 - (1) - 2

f(1) = 1 - 1 - 2

f(1) = -2